2022
DOI: 10.1001/jamanetworkopen.2021.47454
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Polycystic Ovary Syndrome in Patients With Pediatric Type 2 Diabetes

Abstract: IMPORTANCEThe prevalence of pediatric type 2 diabetes (T2D) is increasing globally. Girls with T2D are at risk of developing polycystic ovary syndrome (PCOS), but the prevalence of PCOS among girls with T2D is unknown. OBJECTIVE To determine the prevalence of PCOS in girls with T2D and to assess the association of obesity and race with this prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 73 publications
0
30
0
1
Order By: Relevance
“…Institutional Review Board approval and informed consent were not obtained because the data were anonymous and publicly available. This study was drafted and reported based on the guidelines of a meta-analysis of observational studies in epidemiology (MOOSE) ( 27 , 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…Institutional Review Board approval and informed consent were not obtained because the data were anonymous and publicly available. This study was drafted and reported based on the guidelines of a meta-analysis of observational studies in epidemiology (MOOSE) ( 27 , 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the presence of insulin resistance should reinforce the screening of adolescents for type 2 diabetes as a comorbidity [ 118 ]. There is a high incidence of type 2 diabetes in adolescents with PCOS [ 6 , 119 ] and both diabetes and PCOS increase risk of other comorbidities such as depression during adolescence [ 120 ].…”
Section: Main Criteria To Diagnose Pcos During Adolescencementioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is one of the most common endocrine conditions, affecting 8–13% [ 1 ] of women and 3.4–19.6% of adolescent girls, depending on the diagnostic criteria used and population studied [ 2 , 3 , 4 , 5 , 6 ]. The highest prevalence (19.6%) was reported in adolescents with Type 2 diabetes [ 6 ]. PCOS is also a familial condition with twin studies indicating that hereditability is approximately 70% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a complex endocrine disorder that occurs in 1.14% to 11.04% of adolescent girls globally. [1][2][3] The diagnostic criteria for PCOS in adolescence include the combination of menstrual irregularities according to time since menarche and clinical or biochemical hyperandrogenism but only after excluding other causes. [4][5][6][7][8] Pelvic ultrasonography is not recommended for PCOS diagnosis in girls who are less than 8 years since menarche according to international evidence-based guidelines, because it is associated with over-diagnosis of PCOS.…”
Section: Introductionmentioning
confidence: 99%